Agent and Multi-Agent Systems: Technologies and Applications First KES International Symposium, KES-AMSTA 2007, Wroclaw, Poland, May 31-June 1, 2007, Proceedings - Grzech, Adam (Lecture Notes in Artificial Intelligence, 2007)
st This volume contains papers selected for presentation at the 1 KES Symposium on Agent and Multi-Agent Systems - Technologies and Applications (KES-AMSTA 2007), held in Wroclaw, Poland, May 31 - June 1, 2007. The symposium was org- ized by the Institute of Information Science and Engineering, Wroclaw University of Technology, and KES International, as part of the KES Conference Series. The aim of the symposium was to provide an international forum for scientific - search in the technologies and applications of agent and multi-agent systems. Agents and multi-agent systems are related to the modern software which has long been r- ognized as a promising technology for constructing autonomous, complex and intel- gent systems. A key development in the field of agent and multi-agent systems has been the specification of agent communication languages and formalization of - tologies. Agent communication languages are intended to provide standard decla- tive mechanisms for agents to communicate knowledge and make requests of each other, whereas ontologies are intended for conceptualization of the knowledge - main.